Sobre a dependência do rendimento quântico de luminescência intrínseco com a assimetria em complexos do íon Eu(III) - Anesio, Isabela Lira (2020)
The main objective of this work was to test a conjecture about the rise of the intrinsic luminescence quantum yield values with the increase of the asymmetry around the Eu (III) ion, applying the strategy of “Escalate Coordination Anisotropy” (ECA). For that, compounds with the general formula [TEA][Ln(β-dicetonate)4] and [Ln(β-dicetonate)3(fen)] were synthesized, making two series of compounds for the study. For their characterization, complexometric titration, elementary analysis of Carbon, Hydrogen and Nitrogen techniques, absorption spectroscopy in the infrared region and thermogravimetric analysis were used. In order to characterize the photophysical properties, luminescence spectra were investigated for Gd (III) analog complexes and excitation and emission spectra for Eu(III) complexes. The intrinsic quantum yields were calculated from the luminescence spectra for Eu(III) complexes in solution and in the solid-state (300K). Violation of the aforementioned conjecture was observed for cases in which the complex is in the solid-state, in the two series of complexes investigated. In the case of the complexes in solution, a sharp drop in the value of the intrinsic luminescence quantum yield was observed for one of the complexes.